A miniaturized solid‐phase extraction adsorbent of calix[4]arene‐functionalized graphene oxide/polydopamine‐coated cellulose acetate for the analysis of aflatoxins in corn. Issue 20 (26th August 2018) - Nurerk, Piyaluk; Bunkoed, Warapon; Kanatharana, Proespichaya; Bunkoed, Opas
Abstract: A calix[4]arene‐functionalized graphene oxide/polydopamine‐coated cellulose acetate adsorbent was fabricated for the pre‐concentration of aflatoxins. The highly porous developed adsorbent does not produce the high backpressure that normally occurs in particle‐packed cartridges and its large surface area helps to improve adsorption. The highly efficient adsorption of aflatoxins by the hybrid adsorbent is facilitated via hydrogen bonding and hydrophobic and π‐π interactions. Polymerization time, amount of calix[4]arene‐functionalized graphene oxide, type and volume of desorption solvent, sample pH, sample volume, and sample flow rate were optimized. The linearity of aflatoxin B1 was in the range of 0.01–10.0 μg/kg, aflatoxin B2 was in the range of 0.02–10.0 μg/kg and aflatoxin G1 and aflatoxin G2 were in the range of 0.050–10.0 μg/kg. The limits of detection were 0.01 μg/kg for aflatoxin B1, 0.02 μg/kg for aflatoxin B2 and 0.05 μg/kg for aflatoxin G1 and aflatoxin G2. The developed calix[4]arene‐functionalized graphene oxide/polydopamine‐coated cellulose acetate adsorbent was successfully utilized for the analysis of aflatoxins from corn samples and the extraction efficiency was satisfactory with obtained recoveries from 83.0 to 106.7%. Moreover, fabricated adsorbent is easy to prepare, inexpensive, and can be reused.